Genetic Variability, Correlation and Path Analysis in Mungbean (Vigna radiata L) - Alom, KM Muzibul; Rashid, MH; Biswas, M (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted at the Regional Agricultural Research Station (RARS), BARI, Rahmatpur, and Barisal during the period from January, 2013 to April, 2013 to study on the variability, heritability, genetic advance and interrelationship via correlation coefficient and path coefficient analysis among the important eight characters in relation to seed yield. Significant variation was observed among the studied 54 mungbean genotypes for all characters. Different genotypes were found superior for different characters. Among the genotypes, ACC12810002 for plant height (71.80 cm), TPK255897 for days to 50% flowering (48.67 days as minimum), BC696088 and VO1558 (BG) for days to pod maturity (89.00 days as minimum), VC6149 (B12) for pod length (17.30 cm), ACC12810006 for pods plant1 (31.73), ACC12890073 for seeds pod1 (17.60), VC696088 for 100 seed weight (5.63 g) and GK40 for seed yield (1846.00 kg ha1) were found to be the superior genotypes. Including seed yield, all the characters, except seeds pod1 exhibited high heritability accompanied by medium to high genetic advance as percent of mean. These characters also showed medium to high GCV and PCV. However seeds pod1 showed moderate heritability and genetic advance as present of mean. In all these case significant genotypic correlation coefficient were found to be higher than their corresponding phenotypic ones. The character 100seed weight showed significant positive relationship with seed yield. Path co efficient analysis suggested that pods plant1 contributed maximum direct effects having positive on seed yield. Plant height, pod length and 100seed weight had also positive direct effect on seed yield. Thus selection based on pods plant1, days to first flowering, plant height and 100seed weight might be effective for improving seed yield in mungbean. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22161 J. Environ. Sci. & Natural Resources, 7(1): 131-138 2014